STUDI TENTANG PRODUCT KNOWLEDGE DAN KEPUTUSAN PEMBELIAN PADA NOTEBOOK ACER (Studi Kasus pada Mahasiswa Universitas Diponegoro, Semarang) - Lubis, Raja Fajar Perdana; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2015)
Technology devices has been a necessity in every sector in human being nowadays. One of modern devices which grows rapidly is computer. Computer development is shown in each shape variations and usages. After the type of computer that has to be connected with electricity or what we usually call PC desktop, there is portable notebook, a battery-using computer. The emergence of various brands in the notebook industry that offers innovations and new variants with all good features makes competition in the notebook industry is getting tough. Each companies are required to win the competition by getting consumers as many as possible.This research uses buying decision as a dependent variable, advertising activity, public relation activity, sales credibility, references groups as independent variables, as well as product knowledge as an intervening variable. Number of samples are 100 respondents. The sampling technique uses accidental sampling and data analysis methods used were descriptive statistics, validity test, reliability test, classic assumption test, multiple linear regression and hypothesis testing. Based on the results of the regression analysis showed that the activity of advertising and reference groups has a significant positive effect on product knowledge, however the sales credibility and public relations activities has no significant effects on product knowledge.